2022
DOI: 10.1017/jfm.2022.863
|View full text |Cite
|
Sign up to set email alerts
|

The effect of slip on the development of flow separation due to a bump in a channel

Abstract: A numerical study on the effect of surface slip on the flow in a constricted channel is presented, with the aim of exploring the use of surface slip to control flow separation. Our focus is on two-dimensional flow in a channel over a bump, with a fixed aspect ratio, upon which a Robin-type slip boundary condition is imposed. When the channel walls are fully no-slip, such a flow is known to develop a region of separation behind the bump, at sufficiently large Reynolds numbers. The effect of slip on the separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Indeed, this was achieved for slip lengths 𝜆 = 0.15 and 𝜆 = 0.1 for the respective wide and narrow gap deformations. Thus, similar to Ceccacci et al (2022a) for two-dimensional bumps in a channel, slip provides an effective control mechanism for flow separation in a dilated channel. Moreover, the slip length, 𝜆, required here to achieve flow separation control is less than that needed for the bump configuration.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Indeed, this was achieved for slip lengths 𝜆 = 0.15 and 𝜆 = 0.1 for the respective wide and narrow gap deformations. Thus, similar to Ceccacci et al (2022a) for two-dimensional bumps in a channel, slip provides an effective control mechanism for flow separation in a dilated channel. Moreover, the slip length, 𝜆, required here to achieve flow separation control is less than that needed for the bump configuration.…”
Section: Discussionmentioning
confidence: 89%
“…The main qualitative conclusion drawn from this analysis is that slip provides a mechanism for flow control in a dilated channel as it reduces the intensity and dimensions of the separation bubble that forms within the gap region. Moreover, comparing the observations for the gap geometry with those similar-sized bump configurations modelled by Ceccacci et al (2022a), a smaller slip length, 𝜆, is required to suppress the formation of separated flow in gap concavities than along the rear side of bump deformations. In their investigation, Ceccacci and co-workers showed that 𝜆 ≈ 0.2 was necessary to inhibit reversed flow forming downstream of the two-dimensional Gaussian-shaped bump when the Reynolds number Re = 4000.…”
Section: Effect Of Slip Applied Along the Smooth Depressionmentioning
confidence: 96%
See 3 more Smart Citations